Digital tools and meaning making in mathematics - Manshadi, Saeed (2016)
Presentation from ETEII, 2nd conference on international approaches to scaling-up professional development in maths and science education . Arranged by MASIL, DZLM, Deutsches Zentrum Für Lehrerbildung Mathematik. In Freiburg, 07.11.16 - 09.11.16. This presentation is based upon a school-initiated project: with open doors to the world - A pilot on the use of technology in education at school. The project is interdisciplinary and involves 1. – 4. grade at an elementary school in Northern Norway. Researchers from the Arctic University of Norway have collaborated closely with the participating teachers in the school. The research group represents researches from mathematics education, Norwegian language and pedagogic. The project aims to increase pupils’ achievement in both mathematics and Norwegian language by applying educational technology extensively in teaching classroom at grade 1-4, four classes totally.